Widespread translational control contributes to the regulation of Arabidopsis photomorphogenesis - Ming‐Jung Liu; Szu‐Hsien Wu; Ho‐Ming Chen; Shu‐Hsing Wu (Molecular Systems Biology)
Abstract Environmental ‘light’ has a vital role in regulating plant growth and development. Transcriptomic profiling has been widely used to examine how light regulates mRNA levels on a genome‐wide scale, but the global role of translational regulation in the response to light is unknown. Through a transcriptomic comparison of steady‐state and polysome‐bound mRNAs, we reveal a clear impact of translational control on thousands of genes, in addition to transcriptomic changes, during photomorphogenesis. Genes encoding ribosomal protein are preferentially regulated at the translational level, which possibly contributes to the enhanced translation efficiency. We also reveal that mRNAs regulated at the translational level share characteristics of longer half‐lives and shorter cDNA length, and that transcripts with a cis‐element, TAGGGTTT, in their 5′ untranslated region have higher translatability. We report a previously neglected aspect of gene expression regulation during Arabidopsis photomorphogenesis. The identities and molecular signatures associated with mRNAs regulated at the translational level also offer new directions for mechanistic studies of light‐triggered translational enhancement in Arabidopsis.